Knowledge acquisition, knowledge management strategy and innovation: An empirical study of Vietnamese firms - Nguyen Ngoc Thang; Pham Anh Tuan; Yin Moses (Cogent Business & Management, 2020)
This paper examines two alternative views-universal and contingency- of the knowledge acquisition and innovation relationship in Vietnamese firms. Results from a survey of 130 companies show that knowledge acquisition has a positive effect on innovation. In addition, this study showed that in terms of direct effects on innovation results, the personalization strategy has a more important role than the codification strategy. However, among the two knowledge manage-ment (KM) strategies, only the codification strategy moderated the knowledge acquisition-innovation relationship. The findings also suggested that in order to achieve a high level of innovation results, the firm should not be overly dependent on the implementation of the codification strategy without paying due attention to personalization strategy. Furthermore, for firms at the nascent stage of develop-ment or those in developing countries like Vietnam, knowledge acquisition and personalization strategy can lead to innovation results.
Keywords: 650; Knowledge acquisition; codification strategy; personalization strategy; innovation